Antimicrobial resistance in sexually transmitted infections beyond gonococcal infection - Diogo de Sousa; João Borges- (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Sexually transmitted infections (STIs) show a worldwide growing trend, with a rising incidence in recent years. Although most STIs are not usually lethal, their burden of disease is not negligible resulting in an important health and economic burden worldwide. Neisseria gonorrhoeae antimicrobial resistance (AMR) is recognized as a major health concern, with targeted public health response plans worldwide. However, almost all STIs, including syphilis, trichomoniasis, chlamydia, herpes simplex virus (HSV) infection, and Mycoplasma genitalium infection, have resistances described in the literature, with no structured public health response to assess resistances. This work aims to provide a comprehensive review of AMR within STI beyond gonococcal infection, providing information on prevalence, testing, and treatment recommendations on syphilis, chlamydia, Trichomonas vaginalis infection, M. genitalium infection, and HSV infection. STIs resistance surveillance must rely on a strong network of case reporting, prevalence analysis, assessment of the etiology of STI syndromes, and monitoring of resistances, to prevent the dissemination and emergence of new resistances.